«Né scolorò le stelle umana cura». Poesia e Filosofia nello Zibaldone di Giacomo Leopardi - Meattini, Valerio (Bollettino Filosofico, 2017)
The relationship between poetry and philosophy is a crucial “place” of Zibaldone, finally culminating in the declaration of complementarity between these two summits of the human spirit. The intensity (“very ardent”) with which the poet feels and lives as the said nature must find the equivalent in the opposed intensity (“very cold”) with which the philosopher reflects. Therefore, where feelings and reasoning connect each other and we reason with our entire body, we can come to the “great and general” truths. Philosophy is not just a process of eliminating mistakes but also, combined with philosophy (“poet” and “philosopher” are the same in two different times and modes), the highest degree of understanding of reality, fueled by the most deep and intrinsic nature that is poetry.